Hybrid molecular graphene transistor as an operando and optoelectronic platform - Jorge Trasobares; Juan Carlos Martín-Romano; Muhammad Waqas Khaliq; Sandra Ruiz-Gómez; Michael Foerster; Miguel Ángel Niño; Patricia Pedraz; Yannick. J. Dappe; Marina Calero de Ory; Julia García-Pérez; María Acebrón; Manuel Rodríguez Osorio; et al. (Nature Communications, 2023)
Molecular electronics represents an avenue to enrich conventional electronics, but its reproducibility and scalability are still challenging. Here, the authors report the realization of multifunctional hybrid molecular graphene field effect transistors enabling operando spectroscopy and the implementation of optoelectronic logic gates.